Dentures and good oral health - Abidin, Sulhi (New Straits Times Press (M) Bhd., 2018)
Dentures should be well-fitted and properly maintained for maximum benefit. Denture wearers need to aware of the importance of keeping their dentures clean and safe. They need to know the situations where dentures cannot be worn. They also need to comply with the guidelines as to ensure the dentures are safe to be used.